Effect of implant-abutment emergence profile configuration on peri-implant bone remodeling: A radiographic study - Tsai, Tingyun. (Tufts University. Tisch Library., 2022)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Posthodontics.; Advisor: Andre De Souza.; Committee: Yong Jeong Kim, Matthew Finkelman, and Khaled El Rafie.; Keyword: Dentistry.